Banking industry concentration and net interest margins (NIMs) in Pakistan - Hussain, Ijaz (Journal of Business Economics and Management, 2014)
This paper uses bank level data of 26 commercial banks for the period 2001–2010 to explore determinants of net interest margins of commercial banks of Pakistan. Based on results of this study, past net interest margins, bank soundness, operating cost, industry concentration, relative market share, inflation, real depreciation and industrial growth have statistically significant and positive impact while diversification, change in bank size, lagged liquidity, stock market development have dampening effects on net interest margins. However, impact of ownership, GDP and credit market development is statistically insignificant.Our regression results suggest that stock market development as means of alternative source of finance contributes to reduction in net interest margins while the impact of banking sector development on breaking banking cartels and bringing net interest margins down had been insignificant. Exchange rate adjustments, rate of inflation and growth of the industry also cannot be ignored in management of net interest margins. Incentives for bank executives and managers to ensure efficiency in operating costs, reduction in the premium charged for bank soundness, diversification of bank activities and passing on the scale efficiencies to both depositors and borrowers can also play role to bring interest margins down to accelerate investment and growth in the country.First published online:  16 Jan 2013